PEPELAKSANAAN LELANG EKSEKUSI OBJEK HAK TANGGUNGAN BERDASARKAN PMK NOMOR 213/PMK.06/2020 TENTANG PETUNJUK PELAKSANAAN LELANG (Studi Kasus Putusan Nomor 12/Pdt.Plw/2019/PN.Pbr) - Tomi Yoshua Pardede; Rika Lestari; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Auction activities are sales that of er lower or lower prices. The definitionof auction in Article 1 point 1 PMK Number 213/PMK.06/2020 concerningAuction Implementation Instructions: “An auction is a sale of goods that are opento the public with a written and/or verbal price of er that is increasing ordecreasing to reach the highest price, preceded by the announcement of theauction”. This study aims to find out how the procedure for implementingmortgage auctions is carried out and to find out the obstacles in the process ofimplementing mortgage auctions at the Pekanbaru State Property and AuctionService Of ice. The type of research used is Sociological Law research, Sociologicalresearch with primary and secondary data types using qualitative data analysistechniques. The results of this study are first to find out the auction procedure formaterial guarantees that have been tied with mortgages as part of the executionof debt guarantees by a creditor who has been guaranteed by the debtor andinstalled Mortgage by the creditor. Second, to find out and analyze the Obstaclesin the Implementation of the Auction of Mortgage Objects Based on PMK Number213/PMK.06/2020 concerning Instructions for the Implementation of Auctions. Suggestions that the author can give in this research: Firstly, PekanbaruKPKNL and Auction Of icials in carrying out auctions can verify more carefullythe object to be executed. Comprehensive initial verification in terms of theprocess that has carried out the imposition of mortgage rights by creditors canminimize pre-auction and post-auction problems. The two Parties to thePekanbaru State Property and Auction Service Of ice suggest that the bankingsector be more careful in making mortgage auction announcements in order toanticipate unwanted events that can cause losses to the banking sector